Dabrafenib plus trametinib is effective in the treatment of BRAF V600-mutated metastatic melanoma patients: analysis of patients from the dabrafenib plus trametinib Named Patient Program (DESCRIBE II). Issue 3 (June 2020) - Atkinson, Victoria; Sandhu, Shahneen; Hospers, Geke; Long, Georgina V.; Aglietta, Massimo; Ferrucci, Pier F.; Tulyte, Skaiste; Cappellini, Gian Carlo Antonini; Soriano, Virtudes; Ali, Sayed; Poprach, Alexandr; Cesas, Alvydas; et al.
Abstract : In clinical trials, dabrafenib plus trametinib improved overall survival (OS) compared with single-agent BRAF inhibitors (BRAFi) in patients with BRAF V600-mutant unresectable or metastatic melanoma. We investigated dabrafenib plus trametinib therapy in a compassionate-use setting [Named Patient Program (NPP); DESCRIBE II]. A retrospective chart review of patients with BRAF V600-mutated unresectable stage III/IV melanoma receiving dabrafenib plus trametinib as compassionate use was conducted. Treatment patterns and duration, clinical outcomes, and tolerability were evaluated. Of 271 patients, 92.6% had stage IV melanoma, including 36.5% with brain metastases. Overall, 162 patients (59.8%) were BRAFi naive and 171 (63.1%) received first-line dabrafenib plus trametinib. Among BRAFi-naive patients, the overall response rate (ORR) was 67.3%, median OS (mOS) was 20.0 months, and median progression-free survival (mPFS) was 7.5 months. In BRAFi-naive patients with known brain metastases ( n = 62), ORR was 61.3%, mOS was 15.5 months, and mPFS was 6.2 months. Eighty-four patients received BRAFi monotherapy for >30 days and switched to dabrafenib plus trametinib prior to progression. Of these 84 patients, 63 had known disease status at the time of switch, and 22 improved with the combination therapy. No new safety signals were identified, and dabrafenib plus trametinib was well tolerated. Dabrafenib plus trametinib showed substantial clinical activity in NPP patients with BRAF V600-mutated unresectable or metastatic melanoma. Analysis of treatment patterns demonstrated the effectiveness of the combination in patients with brain metastases and across lines of therapy with a well tolerated and manageable safety profile. Abstract : Supplemental Digital Content is available in the text.